GRAPHICAL ANALYSIS OF DAMAGE MECHANICS MODEL OF CANCER - Oyesanya*, M. O.; Nkuturum†, C. (International Journal of Mathematical Analysis and Modelling, 2023)
This study exposed the action of oxidative stress on the matrix wall that had tumor (voids), that led to cancer and it illustrated the initiation, growth and coalescence of cancer. The analytic solution showed that the magnitude of stress that led the tumor to rupture was 250kN and the time taken to rupture was 100days. The solution showed that the environmental factor that affected the tumor that led to rupture (cancer) was temperature given as  between 0 0 85 100 c. The model result also showcased that the amplitude of the stress in the tumor that led to coalescence was 2000kN and the time taken to coalescence was 100days. Finally, the solution to the model ascertained that it took between 80 -100days for the stress to act on a tumor tissue before it ruptures. Graphs were plotted to illustrate the following actions: rate of growth of cancer cells against the rate of destruction of cells by the cancer cell, the amount of stress applied on tumor against the time taken for tumor to rupture, the amount of stress that will lead solid tumor to coalescence to form cancer. Finally, the analytic solution of the study demonstrates that cancer cells exist right in the solid tumor as a result of oxidative stress losing its bonding power. The system showed significant effect and was found to be stable with growing cancer cells. The study elucidated that the model equations were found physically existing in a disease called ‘‘Acha – Ero or (N’shi Calabar)’’ and MATlab R2015a was used in plotting the graphs.